Strategi Event Perkumpulan Beon Tek Bio Terhadap Festival Peh Cun di Kota Tangerang - David Soni Oksapianus; Mochammad Mirza; Ukon Furkon Sukanda; Alamsyah Alamsyah (Social Science Academic, 2024)
Tambur Peh Cun is a tradition in the form of a festival that still continues today among the Chinese community in Tangerang, Banten. The term Peh-Cun means “boat racing” in Hokkien and consists of two words “Peh” which means “Paddle” or “Paddle” and “Cun” which means “Boat”. Tambur Peh-Cun or also known as "Gou", is one of a series of Peh-Cun ceremonies which is always celebrated on May 5 in the Confucian calendar. Qualitative Research with a Case Study Approach. According to Muhadjir, Qualitative Research is research that prioritizes issues of process and meaning/perception, where this research is expected to reveal various Qualitative information with thorough and meaningful descriptions and analysis, which also does not reject Quantitative information in the form of numbers or amounts. The research was carried out in several stages. The first stage begins with collecting information and observing the research location, then making appointments with resource persons and starting interviews, and preparing the final research report. This research aims to discuss the event strategy held by the Beon Tek Bio Association at the Peh Cun Festival in Tangerang City in 2023. This research uses qualitative research methods with a case study approach to understand and analyze the strategies implemented. Peh Cun is one of the most important festivals in Chinese culture. This festival is celebrated every 5th of the 1st month of Chinese New Year to commemorate the return of Dewa Nian, who is believed to be a god who brings disaster. The Beon Tek Bio Association has implemented a planned and structured event strategy in organizing the Peh Cun Festival in Tangerang City in 2023. This strategy includes aspects -aspects of goals and target audience, program content, and marketing. In terms of program content, the Beon Tek Bio Association presents various interesting and diverse Chinese cultural events. These events are designed to attract public interest and attention, as well as to introduce Chinese culture to the wider community.